Statistical Analysis of Annual DNI Distribution and its Impact on Bankability Assessment for Concentrated Solar Power Plants - Miguel Larrañeta; Jose A López-Álvarez; Elena Pérez-Aparicio; Jose M. Delgado-Sanchez; Joaquín Alonso-Montesinos; Silva-Pérez Manuel A. (SolarPACES Conference Proceedings, 2024)
The Weibull distribution is commonly accepted as the most suitable model for describing the annual distribution of Direct Normal Irradiance (DNI). However, when the annual DNI is assumed to follow a Normal distribution instead of a Weibull distribution, there is a notable increase in the cumulative annual values for unfavourable and worst-case scenarios. In this research, we assess the suitability of different statistical indexes for goodness-of-fit by applying them to the annual cumulative DNI and Global Horizontal Irradiance (GHI) data recorded at six locations with varying climates. Our observations reveal that, across all locations, the Representative Solar Year (RSY) aligns with the 50% Probability of Exceedance (PoE50) of a Normal distribution fitted to the observed data. We quantify that assuming the annual DNI conforms to a Weibull distribution, as opposed to a Normal distribution, results in a substantial decrease of approximately 7% in the annual cumulative value for the worst-case scenario. Based on our analysis, we find no compelling evidence to reject the hypothesis that the annual DNI follows a Normal distribution.